Dad's army [videorecording (DVD)] - Zeta-Jones, Catherine, 1969-; Nighy, Bill, 1949-; Gambon, Michael; Parker, Oliver (Universal Studios Home Entertainment, 2016)
It's 1944 and WWII is reaching its climax. The Allies are poised to invade France and finally defeat the German army. Morale in the Walmington-on-Sea Home Guard is low, so they make their new mission to revive spirits, until glamorous journalist Rose arrives to write about their exploits.